TREATMENT OF CHRONIC GASTRITIS IN CARRIERS OF VARIOUS GENOTYPES - Ochilova Gulrukh Saidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Resume: The MDR1 gene promotes binding of the cell to the drug, its entry into the cell, and /or efflux into the intercellular space, which explains the development of resistance of the cell to drugs during the expression of this gene. Therefore, the MDR1 gene plays an important role in the effectiveness of pharmacotherapy of various diseases, including HCG. The MDR-1 gene encodes the protein P-glycoprotein (translated from the English "permeability" means "permeability"), which is located in the membrane of many normal cells of organs and tissues of the body and regulates the processes of active absorption of drugs through the membrane into the cell. The expression of this protein determines the pharmacokinetics of drugs and, at one time, the effectiveness of pharmacotherapy.